Arsenic, iron, and manganese in groundwater and its associated human health risk assessment in the rural area of Jashore, Bangladesh. (2nd June 2022) - Chakraborty, Tapos Kumar; Ghosh, Gopal Chandra; Ghosh, Prianka; Jahan, Israt; Zaman, Samina; Islam, Md. Shahnul; Hossain, Md Ripon; Habib, Ahsan; Biswas, Biplab; Sultana, Naznin; Khan, Abu Shamim
Abstract: This study investigated groundwater pollution and potential human health risks from arsenic, iron, and manganese in the rural area of Jashore, Bangladesh. Study results show that the mean value of groundwater pH is 7.25 ± 0.31, with a mean conductivity of 633.94 ± 327.41 μs/cm, while about 73, 97, and 91% of groundwater samples exceeded the Bangladesh drinking water standard limits for As, Fe, and Mn, respectively. Groundwater pollution evaluation indices, including the heavy metal pollution index, the heavy metal evaluation index, the degree of contamination, and the Nemerow pollution index, show that approximately 97, 82, 100, and 100% of samples are in the high degree of pollution category, respectively. Spatial distribution exhibited that the study area is highly exposed to As (73%), Fe (82%), and Mn (46%). In the case of non-carcinogenic health risk via oral exposure, about 94% of samples suggest a high category of risk for infants, and 97% of samples are found to be at high risk for children and adults. The carcinogenic risk of arsenic via an oral exposure pathway suggests that approximately 97% of the samples are found to be at high risk for infants, and all of the samples are at high risk for both adults and children. HIGHLIGHTS: Shallow groundwater samples were collected from the rural area, Jashore, Bangladesh. The study area is highly exposed to As (73%), Fe (82%), and Mn (46%). Pollution evaluation indices exhibit a high degree of pollution. Infants, adults, and children have significant non-carcinogenic and carcinogenic health risks via oral ingestion. Sensitivity analysis revealed that concentration is mainly responsible for carcinogenic risk.